SOME CONSEQUENCES OF THE BINDING OF AFLATOXIN B1 WITH PLASMA MEMBRANE ON THE REGULATION OF INTRACELLULAR Ca2+ HOMEOSTASIS (1992)
The possible influence of aflatoxin B1 a potent hepatocellular carcinogen on the regulation of intracellular Ca2+ homeostasis has been studied using the red cell as a model. Preliminary work on the interaction of the toxin with the red cell membrane using spectrofluometric analysis indicated that the toxin binds spontaneously and irreversibly to the red cell membrane. The binding is highest at pH 4 and least at pH 10. Results obtained from studies using equilibrum dialysis technique show that about 4 nmoles of the toxin bind to one microgram membrane protein. Although the exact membrane component to which aflatoxin B1 binds is not known, experiments carried out to determine the influence of aflatoxin B1 on the activity of the calcium pumping protein revealed that the toxin inhibited the calmodulin-stimulated erythrocyte membrane Ca2+ -ATPase activity by about 50 percent, while it has little or no effect on its basal activity. Kinetic analysis of the inhibition shows that, the toxin reduces the Vmax and Km of the calmodulin-stimulated enzyme by 50 percent in a non-competitive manner, On the other hand, the carcinogen had no significant influence on the kinetic parameters of the enzyme in the non-activated state. Similar results were obtained for the triton X-100 solubilized and calmodulin affinity chromatographed enzyme. In this instance aflatoxin B1 inhibited the calmodulin-stimulated purified enzyme by 50 percent with or without preincubation on ice for half an hour. Again, the toxin had little or no effect on the basal activity of the enzyme in the absence of calmodulin. Analysis of the results obtained using varying concentrations of ATP shows that the Km and Vmax of the non-activated enzyme were not altered by the toxin while both the Vmax and Km values were reduced by about 50 percent in the presence of calmodulin. In addition aflatoxin B1 inhibited Diphosphotidyl glycerol (cardiolipin) by about 28% while it has no effect on the basal activity of the enzyme. Although, the inhibition of the membrane bound or purified Ca2+ ATPase by the toxin is concentration dependent, varying concentrations of phosphatidyl serine and phosphatidyl choline do not affect the inhibition of the purified enzyme by afla toxin B1. Results obtained with triton X-100 solubilized enzyme shows that triton X-100 alone could not activate the enzyme. Thus at triton X-100: protein ratio of 2, the enzyme was stimulated by calmodulin. This activity was sensitive to inhibition by the toxin. In this instance, the calmodulin-stimulated activity was inhibited by about 50%, while at lower ratios of the triton X-100 to protein there was no significant inhibition of enzyme. Results of experiments carried out on the 124KDa fragment, which was produced as a result of exposure to calpain a Ca2+ - dependent cysteine protease, indicated that the toxin has no effect whatsoever on the activity of the fragmented enzyme, Similarly experiments on limited proteolysis of the Ca2+ ATPase by trypsin to give the 90KDa fragment which still retains its calmodulin binding domain and the 76KDa fragment which has lost its calmodulin binding domain revealed that the aflatoxin inhibited the 90KDa fragment by about 50% while the 76KDa fragment is not affected at all. Altogether, -these findings show that aflatoxin B1 inhibits the plasma membrane Ca2+ - pumping ATPase by interacting with the enzyme at the calmodulin binding domain. The nature of the exact amino acid residue to which the toxin binds is however not known. The implication of these observations is that Ca2+ extrusion may be hampered in situations where the cell is poisoned by the aflatoxin